2017
DOI: 10.24200/sci.2017.4418
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical reinforcement of urinary bladder matrix by electrospun polycaprolactone nanofibers

Abstract: Abstract. For a successful repair and reconstruction of bladder tissue, fabrication of sca olds with proper biochemical and biomechanical characteristics is necessary. Decellularized bladder tissue has been proposed in previous studies as a gold standard material for sca old fabrication. However, weak mechanical properties of such a loadbearing tissue has remained a challenge. Incorporation of both biological and synthetic materials has been known as an e ective strategy for improving mechanical and biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…To this end, PCL scaffold was embedded in rat acellular bladder ECM hydrogel and then the construct was freeze-dried. The resultant hybrid scaffold indicated considerably improved mechanical strength compared to ECM sponge, and contrary to the sponge it could be utilized in surgery ( Ghafari et al, 2017 ). Using a relatively similar strategy, Ajalloueian et al constructed a hybrid scaffold with electrospun PLGA and collagen.…”
Section: Electrospinning For Bladder Tissue Engineeringmentioning
confidence: 99%
“…To this end, PCL scaffold was embedded in rat acellular bladder ECM hydrogel and then the construct was freeze-dried. The resultant hybrid scaffold indicated considerably improved mechanical strength compared to ECM sponge, and contrary to the sponge it could be utilized in surgery ( Ghafari et al, 2017 ). Using a relatively similar strategy, Ajalloueian et al constructed a hybrid scaffold with electrospun PLGA and collagen.…”
Section: Electrospinning For Bladder Tissue Engineeringmentioning
confidence: 99%
“…Several groups have incorporated elastin to develop highly elastic biomaterials, with the caveat that most methods include crosslinkers that are inherently cytotoxic (i.e., glutaraldehyde, hexamethylene diisocyanate) [ 16 ]. Other strategies used either peptide materials [ 17 , 18 , 19 ] or micro/nanofiber reinforced materials [ 20 , 21 ] to enhance elasticity and compliance; however, they are still unable to match the high extensibility of the urinary bladder. The inability of these materials to recapitulate the biomechanics of the bladder warrants further investigation into other mechanisms of elasticity and compliance, such as tissue ultrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…Using scanning electron microscopy (SEM), Murakumo et al identified a unique helical architecture of collagen type III within the bladder, suggesting a role of collagen architecture in its biomechanics [ 13 ]. Although some groups have incorporated micro/nanofibers [ 20 , 21 ] into the material, the fibers are deposited in its fully elongated state and simply act to increase tensile strength instead of compliance. While it is possible to electrospin intertwined nanofibers [ 22 ], the authors of the study did not apply their technique in scaffold construction.…”
Section: Introductionmentioning
confidence: 99%